3D porous material, preparation method thereof and application of 3D porous material in electro-catalytic furfural hydrogenation
By preparing CuPd alloys and using gas-phase dealloyment technology to form a 3D porous structure, combined with cyclic voltammetry treatment, the problems of complex preparation and poor stability of existing copper-based catalysts are solved, and efficient furfural electrocatalytic hydrogenation reaction is achieved, reducing raw materials Cost and improve catalytic performance.
Patent Information
- Application Number
- CN202411308418.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
AI Technical Summary
The existing copper-based catalysts have problems such as complex preparation methods and poor catalytic stability in furfural catalytic hydrogenation, and the precious metal catalysts are costly, and the electrocatalytic activity and selectivity of single metal copper are poor.
CuPd alloy is prepared and a 3D porous CuPd alloy is obtained by gas-phase dealloyment technology, followed by cyclic voltammetry treatment to improve catalytic activity and reduce costs to form a regular porous structure.
It has achieved simplification of the preparation process, reduced production costs, improved catalytic performance and stability, significantly improved the utilization rate of precious metals, and is suitable for electrocatalytic hydrogenation reaction of furfural.
Smart Images

Figure HDA0005049946730000011 
Figure HDA0005049946730000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porous material preparation, and specifically relates to a 3D porous material and a preparation method thereof and application in electrocatalytic furfural hydrogenation. Background Art
[0002] Furfural is a common agricultural and forestry chemical product that can be obtained by hydrolysis of agricultural and forestry by-products. The main product of its catalytic hydrogenation is furfural alcohol. Furfural alcohol is a common industrial chemical that can be used as a raw material for many chemical products such as resins, adhesives, plastics, and plasticizers. The reaction conditions of electrocatalytic hydrogenation are mild and have high research value compared to traditional hydrogenation reactions. The catalyst is the core of the catalytic reaction, and it is particularly important to develop electrocatalysts with excellent selectivity and high catalytic efficiency.
[0003] Copper is an easily available and inexpensive transition metal element with a suitable redox potential, and is often used to prepare electrocatalysts. However, the electrocatalytic activity and selectivity of single metal copper are poor. Although noble metals have better catalytic activity and selectivity, they are more expensive.
[0004] Porous metal materials are composed of metal skeletons and pores. The porous structure can increase the specific surface area of the material participating in the reaction, reduce density, and improve conductivity. Dealloying is a feasible method for large-scale production of porous metals, which has the advantages of low cost and easy control. However, chemical dealloying, electrochemical dealloying and other dealloying methods require the use of chemical reagents, which have problems such as environmental pollution and high cost.
[0005] At present, some inventions have selected copper-based material catalysts for furfural catalytic hydrogenation. For example, CN106807423A uses copper oxide as the active component and calcium carbonate as the carrier to prepare a copper-containing catalyst for furfural hydrogenation. CN102631930A uses a variety of oxides such as CuO and Cr2O3 to catalyze furfural at a reaction temperature of 120-210°C. CN117960254A prepares copper-silicon catalysts for furfural hydrogenation reaction by roasting, acid leaching, desiliconization, and electrolytic decoppering of copper-based catalysts. The catalysts obtained by the above inventions show good selectivity or activity in furfural catalytic addition, but there are problems such as complex preparation methods and poor catalytic stability, and there is still room for further improvement. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a 3D porous material and a preparation method thereof and application in the electrocatalytic hydrogenation of furfural. The present invention first prepares a CuPd alloy, which is then alloyed with Zn, and then obtains a CuPd 3D porous alloy through a gas phase dealloying technique, so that the alloy material forms a regular porous structure; then, through further cyclic voltammetry treatment, the precious metal is enriched on the surface of the material, thereby improving the catalytic activity and reducing the cost of raw materials. The preparation method of the 3D porous material of the present invention is simpler to operate, has a short production cycle, and can be mass-produced. The 3D porous material prepared by the present invention is applied to the electrocatalytic hydrogenation of furfural, and exhibits excellent catalytic performance.
[0007] The present invention is achieved through the following technical solutions:
[0008] A 3D porous material is a 3D porous CuPd material with a pore size within 10 μm.
[0009] The method for preparing the above 3D porous material comprises the steps of:
[0010] (1) Cu and Pd are mixed uniformly, and alloy foil is obtained by melting, cold rolling and annealing;
[0011] (2) placing Zn on one side of a tube furnace and placing an alloy foil on the other side of the tube furnace, evacuating the tube furnace, and heating to obtain a copper-palladium-zinc alloy; then, demetallizing zinc in an argon-hydrogen mixed gas atmosphere to obtain a 3D porous CuPd alloy;
[0012] (3) The 3D porous CuPd alloy was treated by cyclic voltammetry in a phosphate buffer solution and dried to obtain a 3D porous material.
[0013] Preferably according to the present invention, in step (1), the atomic ratio of Cu to Pd is 90-99.9:0.1-10, preferably 90-95:5-10.
[0014] Preferably, according to the present invention, in step (1), the smelting temperature is 350-360° C., the smelting time is 2-5 minutes, and the smelting is carried out under vacuum conditions.
[0015] Preferably according to the present invention, in step (1), cold rolling is performed to obtain an alloy foil having a thickness of 10 to 100 μm.
[0016] Preferably, in step (1), the annealing temperature is 500-700° C., the annealing time is 2-5 hours, and the annealing is performed in an argon-hydrogen mixed gas atmosphere; the volume ratio of argon to hydrogen in the argon-hydrogen mixed gas is 90-95:5-10. Annealing is performed to eliminate internal stress.
[0017] Preferably according to the present invention, in step (2), the mass ratio of Zn to alloy foil is 2-4:1.
[0018] According to the preferred embodiment of the present invention, in step (2), the heating reaction temperature is 600-700°C and the heating reaction time is 2-3 hours. Zinc provides saturated zinc vapor under heating conditions, and zinc and alloy foil are placed on both sides of the tubular furnace to avoid direct contact between the alloy foil and zinc.
[0019] Preferably, in step (2), the demetallization zinc reaction temperature is 600-700° C., the reaction time is 60-80 minutes; and the volume ratio of argon to hydrogen in the argon-hydrogen mixture is 90-95:5-10.
[0020] Preferably according to the present invention, in step (3), the pH of the phosphate buffer solution is 5-7.
[0021] Preferably, in step (3), the voltage range of the cyclic voltammetry treatment is -0.7 to 1.0 V (relative to the reversible hydrogen electrode), and the treatment is performed until the cyclic voltammetry curves of two adjacent cycles completely overlap.
[0022] According to the preferred embodiment of the present invention, in step (3), the working electrode used in the cyclic voltammetry treatment is a 3D porous CuPd alloy, the reference electrode is a saturated Ag / AgCl electrode, the counter electrode is a platinum wire, and the scanning speed is 10 to 30 mV s -1 .
[0023] Application of the above 3D porous materials in electrocatalytic furfural hydrogenation.
[0024] Preferably, according to the present invention, the application method comprises the steps of: using the 3D porous material as the working electrode, the saturated Ag / AgCl electrode as the reference electrode, the platinum wire as the counter electrode, and the phosphate buffer solution as the electrolyte, and reducing at -1.5V (relative to the reversible hydrogen electrode) for 10 to 20 minutes; adding furfural to the electrolyte and fully dispersing it evenly; and performing an electrocatalytic hydrogenation reaction of furfural at a constant potential.
[0025] Preferably, the pH of the phosphate buffer solution is 5-7.
[0026] Preferably, the concentration of furfural in the electrolyte is 20 to 80 mmol / L.
[0027] Preferably, the constant potential is -0.1 to -0.5 V (vs. reversible hydrogen electrode).
[0028] The technical features and beneficial effects of the present invention are as follows:
[0029] (1) The present invention first prepares a CuPd alloy, then alloys it with Zn, and then obtains a 3D porous CuPd alloy through a vapor phase dealloying technique, so that the metal / alloy material forms a regular porous structure; then, through further cyclic voltammetry treatment, the precious metal Pd is enriched on the surface of the material, thereby improving the catalytic activity while reducing the cost of raw materials. The preparation method described in the present invention can effectively and controllably prepare metal / alloy 3D porous materials with different thicknesses and compositions and regular porous morphologies. The method has a simple production process, a short production cycle, low cost, can be mass-produced, and has significantly improved performance, which is conducive to experimental exploration and further commercial use.
[0030] (2) After the copper-palladium-zinc alloy is prepared in the present invention, the zinc is removed by vapor-phase dealloying technology to prepare a 3D porous CuPd alloy. Compared with chemical dealloying, electrochemical dealloying and other dealloying methods, the vapor-phase dealloying utilizes the difference in saturated vapor pressure between alloy components, and can selectively remove components with high vapor pressure, thereby obtaining a three-dimensional porous structure. The vapor-phase dealloying method reduces the chemical reagents involved, and the evaporated components are easy to collect and recycle, which is environmentally friendly and saves costs, and has great advantages in the production of porous materials.
[0031] (3) The present invention first prepares a 3D porous CuPd alloy, which is beneficial to the subsequent cyclic voltammetry treatment, increases the specific surface area involved in the reaction, leaves a large amount of space for the diffusion of the electrolyte, and is beneficial to mass transfer during the charge and discharge process.
[0032] (4) The 3D porous material of the present invention uses less raw material precious metal Pd. After cyclic voltammetry treatment, the Pd content on the surface is enriched, which is significantly higher than that on the untreated surface, so that the catalytic performance reaches the level of high Pd content. This method improves the utilization rate of precious metals and greatly reduces the cost of raw materials.
[0033] (5) The 3D porous material obtained by the present invention has micron-scale pore morphology, controllable structure, uniform morphology, and a high content of Pd on the surface of the material; it is applied to the electrocatalytic hydrogenation of furfural, and the catalyst has excellent furfural electrocatalytic hydrogenation performance, high Faraday efficiency and furfuryl alcohol production rate. At the same time, the material has good catalytic stability, and the performance can remain stable during long-term use.
[0034] (6) The method for preparing the 3D porous material of the present invention can be extended to prepare porous structures of various other metal / alloy materials. In addition to being used in furfural electrocatalytic hydrogenation, the prepared material can also be used in other electrocatalytic, chemical catalytic and other aspects, and has wide applicability.
[0035] (7) The amount of Zn used in the preparation method of the present invention needs to be appropriate. If the Zn is insufficient, it will lead to uneven pores after dealloying. If the Zn is excessive, the Zn cannot be completely separated during the dealloying process, resulting in the CuPd porous alloy containing too high a Zn content, which is not conducive to improving the catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a surface scanning electron microscope morphology image of the porous material prepared in Example 3.
[0037] Figure 2 This is a cross-sectional scanning electron microscope morphology image of the porous material prepared in Example 3. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0039] In the examples, the raw materials and equipment used are commercially available unless otherwise specified, and the methods used are existing methods unless otherwise specified.
[0040] Example 1
[0041] A method for preparing a 3D porous material comprises the following steps:
[0042] (1) Weigh copper and palladium metal raw materials according to an atomic ratio of 90:10 for later use;
[0043] (2) The raw metals Cu and Pd are mixed evenly, placed in a quartz tube and vacuum-sealed, and formed into an ingot by induction melting at 350°C for 3 minutes. After cooling, the ingot is taken out and cold-rolled into an alloy foil with a thickness of about 50 μm.
[0044] (3) In an argon-hydrogen mixed gas atmosphere (the volume ratio of argon to hydrogen in the argon-hydrogen mixed gas is 93:7), the foil is annealed at 700° C. for 3 hours in a tube furnace to eliminate internal stress, thereby obtaining an alloy foil.
[0045] (4) Place three times the mass of zinc metal particles of the alloy foil on one side of the quartz tube of the tube furnace to provide a saturated zinc vapor environment, and place the annealed alloy foil on the other side to avoid direct contact with zinc. Seal the quartz tube with a glass sheet, evacuate, and heat at 650°C for 2.5 hours to form a copper-palladium-zinc alloy. Under argon-hydrogen mixed gas conditions (the volume ratio of argon and hydrogen in the argon-hydrogen mixed gas is 93:7), the alloy sheet is heated at 650°C in a tube furnace for 70 minutes to remove the metallic zinc and obtain a 3D porous CuPd alloy.
[0046] (5) The prepared 3D porous CuPd alloy was subjected to cyclic voltammetry in 0.5 mol / L phosphate buffer solution (pH 5). The single-side area of the 3D porous CuPd alloy was 0.6 cm -2 The volume of phosphate buffer solution was 40 mL for each of the cathode and cathode chambers. The voltage range used for cyclic voltammetry was -0.7 to 1.0 V (relative to the reversible hydrogen electrode). The working electrode used was a 3D porous CuPd alloy connected by a graphite clip, the reference electrode was an Ag / AgCl (3.5 M KCl) electrode, the counter electrode was a platinum wire, and the scan rate was 20 mV s -1 The treatment was performed until the two adjacent cyclic voltammetry curves completely overlapped, which was considered stable, enriching Pd on the surface, and drying to obtain a 3D porous material.
[0047] The application of the above 3D porous material in the electrocatalytic hydrogenation of furfural is as follows: the 3D porous material is used as the working electrode, the Ag / AgCl (3.5M KCl) electrode is used as the reference electrode, and the platinum wire is used as the counter electrode. A 0.5mol / L phosphate buffer solution (pH 5) is used as the electrolyte, and constant potential reduction is performed at -1.5V (relative to the reversible hydrogen electrode) for 15 minutes. Furfural is added to the electrolyte to make the concentration of the reactant furfural 40mmol / L, and stirred for 10 minutes to fully dissolve it. The electrocatalytic hydrogenation of furfural is performed at -0.3V (relative to the reversible hydrogen electrode).
[0048] When the electrocatalytic hydrogenation reaction was carried out for 120 minutes, the conversion rate of furfural to furfuryl alcohol was about 24%, and the production rate of furfuryl alcohol could reach 0.28 mmol cm -2 h -1 , selectivity reaches 98%, and the Faradaic efficiency of the process is about 43%.
[0049] Example 2
[0050] A method for preparing a 3D porous material is as described in Example 1, except that the atomic ratio of the copper and palladium raw materials used is 95:5; the other steps and conditions are the same as in Example 1.
[0051] The application of the above 3D porous material in electrocatalytic furfural hydrogenation is the same as that in Example 1.
[0052] When the electrocatalytic hydrogenation reaction was carried out for 120 minutes, the conversion rate of furfural to furfuryl alcohol was about 24%, and the production rate of furfuryl alcohol could reach 0.29 mmol cm -2 h -1 , selectivity reaches 99%, and the Faradaic efficiency of the process is about 58%.
[0053] Example 3
[0054] A method for preparing a 3D porous material, as described in Example 1, except that the atomic ratio of the copper and palladium raw materials used is 99:1; the other steps and conditions are the same as in Example 1.
[0055] The application of the above 3D porous material in electrocatalytic furfural hydrogenation is the same as that in Example 1.
[0056] When the electrocatalytic hydrogenation reaction was carried out for 120 minutes, the conversion rate of furfural to furfuryl alcohol was about 16%, and the production rate of furfuryl alcohol could reach 0.24 mmol cm -2 h -1 , selectivity reaches 99%, and the Faradaic efficiency of the process is about 58%.
[0057] The surface scanning electron microscope morphology images and cross-sectional scanning electron microscope morphology images of the porous material prepared in this embodiment are shown in FIG. Figure 1 and 2 As shown. Figure 1 It can be seen that the CuPd porous alloy formed by this method has a uniform pore structure, and its pore size is about 5μm. Figure 2 It can be seen that the thickness of the alloy sheet prepared by this method is about 100 μm.
[0058] Example 4
[0059] A method for preparing a 3D porous material, as described in Example 1, except that the atomic ratio of the copper and palladium raw materials used is 99.9:0.1; the other steps and conditions are the same as in Example 1.
[0060] The application of the above 3D porous material in electrocatalytic furfural hydrogenation is the same as that in Example 1.
[0061] When the electrocatalytic hydrogenation reaction was carried out for 120 minutes, the conversion rate of furfural to furfuryl alcohol was about 7%, and the production rate of furfuryl alcohol could reach 0.09 mmol cm -2 h -1 , selectivity reaches 99%, and the Faradaic efficiency of the process is about 58%.
[0062] Example 5
[0063] A method for preparing a 3D porous material, same as Example 1.
[0064] The application of the above 3D porous material in the electrocatalytic furfural hydrogenation is as described in Example 1, except that the concentration of furfural in the electrolyte is 20 mmol / L; the other steps and conditions are the same as in Example 1.
[0065] Example 6
[0066] A method for preparing a 3D porous material, same as Example 1.
[0067] The application of the above 3D porous material in the electrocatalytic furfural hydrogenation is as described in Example 1, except that the concentration of furfural in the electrolyte is 80 mmol / L; the other steps and conditions are the same as in Example 1.
[0068] Example 7
[0069] A method for preparing a 3D porous material, same as Example 1.
[0070] The application of the above 3D porous material in the electrocatalytic hydrogenation of furfural is as described in Example 1, except that the electrocatalytic hydrogenation of furfural is carried out at -0.2 V (relative to a reversible hydrogen electrode); the other steps and conditions are the same as in Example 1.
[0071] Example 8
[0072] A method for preparing a 3D porous material, same as Example 1.
[0073] The application of the above 3D porous material in the electrocatalytic hydrogenation of furfural is as described in Example 1, except that the electrocatalytic hydrogenation of furfural is carried out at -0.4 V (relative to a reversible hydrogen electrode); the other steps and conditions are the same as in Example 1.
[0074] Comparative Example 1
[0075] A method for preparing a 3D porous material is as described in Example 1, except that in steps (1) and (2), only copper is used as the raw material without adding Pd; the other steps and conditions are the same as in Example 1.
[0076] The application of the above 3D porous material in electrocatalytic furfural hydrogenation is the same as that in Example 1.
[0077] When the electrocatalytic hydrogenation reaction was carried out for 120 minutes, the conversion rate of furfural to furfuryl alcohol was about 0.4%, and the production rate of furfuryl alcohol could reach 0.005 mmol cm -2 h -1 , selectivity reaches 85%, and the Faradaic efficiency of the process is about 7%.
[0078] Comparative Example 2
[0079] A method for preparing a 3D porous material is as described in Example 1, except that step (5) is omitted; the other steps and conditions are the same as in Example 1.
[0080] The application of the above 3D porous material in electrocatalytic furfural hydrogenation is the same as that in Example 1.
[0081] When the electrocatalytic hydrogenation reaction was carried out for 120 minutes, the conversion rate of furfural to furfuryl alcohol was about 13%, and the production rate of furfuryl alcohol could reach 0.01 mmol cm-2 h -1 , selectivity reaches 93%, and the Faradaic efficiency of the process is about 20%.
[0082] Comparative Example 3
[0083] A method for preparing a 3D porous material, as described in Example 2, except that step (5) is omitted; the other steps and conditions are the same as in Example 2.
[0084] The application of the above 3D porous material in electrocatalytic furfural hydrogenation is the same as in Example 2.
[0085] When the electrocatalytic hydrogenation reaction was carried out for 120 minutes, the conversion rate of furfural to furfuryl alcohol was about 2%, and the production rate of furfuryl alcohol could reach 0.03 mmol cm -2 h -1 , selectivity reaches 97%, and the Faradaic efficiency of the process is about 35%.
[0086] Comparative Example 4
[0087] A method for preparing a 3D porous material is as described in Example 3, except that step (5) is omitted; the other steps and conditions are the same as those in Example 3.
[0088] The application of the above 3D porous material in electrocatalytic furfural hydrogenation is the same as that in Example 3.
[0089] When the electrocatalytic hydrogenation reaction was carried out for 120 minutes, the conversion rate of furfural to furfuryl alcohol was about 1%, and the production rate of furfuryl alcohol could reach 0.02 mmol cm -2 h -1 , selectivity reaches 95%, and the Faradaic efficiency of the process is about 32%.
[0090] Comparative Example 5
[0091] A method for preparing a 3D porous material, as described in Example 1, except that: in steps (1) and (2), only copper is used as the raw material without adding Pd; and step (5) is omitted; the other steps and conditions are the same as in Example 1.
[0092] The application of the above 3D porous material in electrocatalytic furfural hydrogenation is the same as that in Example 1.
[0093] When the electrocatalytic hydrogenation reaction was carried out for 120 minutes, the conversion rate of furfural to furfuryl alcohol was about 1%, and the production rate of furfuryl alcohol could reach 0.01 mmol cm -2 h -1 , selectivity reaches 93%, and the Faradaic efficiency of the process is about 18%.
Claims
1. A 3D porous material, characterized in that: The 3D porous material is a 3D porous CuPd material with a pore size within 10 μm.
2. The method for preparing the 3D porous material according to claim 1, comprising the steps of: (1) Cu and Pd are mixed uniformly, and alloy foil is obtained by melting, cold rolling and annealing; (2) placing Zn on one side of a tube furnace and placing an alloy foil on the other side of the tube furnace, evacuating the tube furnace, and heating the tube furnace to obtain a copper-palladium-zinc alloy; then, demetallizing zinc in an argon-hydrogen mixed gas atmosphere to obtain a 3D porous CuPd alloy; (3) The 3D porous CuPd alloy was treated by cyclic voltammetry in a phosphate buffer solution and dried to obtain a 3D porous material.
3. The method for preparing the 3D porous material according to claim 2, characterized in that: In step (1), the atomic ratio of Cu to Pd is 90-99.9:0.1-10, preferably 90-95:5-10.
4. The method for preparing the 3D porous material according to claim 2, characterized in that: In step (1), one or more of the following conditions are included: i. The melting temperature is 350-360°C, the melting time is 2-5 minutes, and the melting is carried out under vacuum conditions; ii. cold rolling to obtain an alloy foil with a thickness of 10 to 100 μm; iii. The annealing temperature is 500-700° C., the annealing time is 2-5 hours, and the annealing is carried out in an argon-hydrogen mixed gas atmosphere; the volume ratio of argon to hydrogen in the argon-hydrogen mixed gas is 90-95:5-10.
5. The method for preparing the 3D porous material according to claim 2, characterized in that: In step (2), the mass ratio of Zn to alloy foil is 2-4:
1.
6. The method for preparing the 3D porous material according to claim 2, characterized in that: In step (2), the heating reaction temperature is 600-700° C., and the heating reaction time is 2-3 hours; Preferably, in step (2), the reaction temperature for zinc removal is 600-700° C., the reaction time is 60-80 minutes, and the volume ratio of argon to hydrogen in the argon-hydrogen mixed gas is 90-95:5-10.
7. The method for preparing the 3D porous material according to claim 2, characterized in that: In step (3), the pH of the phosphate buffer solution is 5-7.
8. The method for preparing the 3D porous material according to claim 2, characterized in that: In step (3), the voltage range of the cyclic voltammetry treatment is -0.7 to 1.0 V (relative to the reversible hydrogen electrode), and the treatment is performed until the cyclic voltammetry curves of two adjacent cycles completely overlap.
9. The method for preparing the 3D porous material according to claim 2, characterized in that: In step (3), the working electrode used in the cyclic voltammetry treatment is a 3D porous CuPd alloy, the reference electrode is a saturated Ag / AgCl electrode, the counter electrode is a platinum wire, and the scanning speed is 10-30 mV s -1 .
10. Application of the 3D porous material as claimed in claim 1 in electrocatalytic furfural hydrogenation; Preferably, the application method comprises the steps of: using the 3D porous material as a working electrode, a saturated Ag / AgCl electrode as a reference electrode, a platinum wire as a counter electrode, and a phosphate buffer solution as an electrolyte, reducing at -1.5V (relative to a reversible hydrogen electrode) for 10 to 20 minutes; adding furfural to the electrolyte and fully dispersing it evenly; and performing an electrocatalytic hydrogenation reaction of furfural at a constant potential; More preferably, the pH of the phosphate buffer solution is 5 to 7; the concentration of furfural in the electrolyte is 20 to 80 mmol / L; and the constant potential is -0.1 to -0.5 V (relative to a reversible hydrogen electrode).
